Jesus and the rise of early Christianity a history of New Testament times - Barnett, Paul William (Downers Grove, IL IVP, 1999)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. -- history of biblical events; Church history -- primitive and early church, ca. 30-600.; Bible. N.T. -- history of contemporary events